Characterization of injection molded polylactide stereocomplexes blended with thermoplastic starch and chain extender - Y Srithep; D Pholharn; O Veang-in; J Morris (My University, 2022)
Abstract Polylactide (PLA) is an interesting biodegradable polymer but has limited application because of its low thermal stability and brittleness. Both weaknesses of PLA were solved by stereocomplexes (ST) blended with thermoplastic starch (TPS). In this work, 15% and 30% TPS and 2% chain extender were blended with poly(L-lactide) (PLLA)/poly(D-lactide) (PDLA) (50/50) in an internal mixer. The blended materials were then injection molded into tensile specimens. Differential scanning calorimetry demonstrated that despite the added starch, the stereocomplex structures were still formed and stereocomplex crystallinity decreased with increasing starch content. Compared to neat PLLA, the melting temperature of the stereocomplex and its starch blends was about 55°C higher. The starch enhanced the elongation at break of the stereocomplex samples. Furthermore, stereocomplex and starch compatibility was improved by extending the chains, which in turn improved the stereocomplex and starch blend mechanical properties.
Keywords: Thermal Stability; biodegradable polymer synthesis and properties